Mitral Valve Repair in Rheumatic Disease: Early Results - Pradhan, S; Koirala, B; Koirala, R; Sharma, J; Acharya, A; Sharma, P (Nepalese Heart Journal, 2004)
Mitral valve repair is an accepted method of treating severe mitral valve disease due to rheumatic fever, Valve repair confers fewer complications and better survival as compared to mitral valve replacement. Since commencing open-heart surgery at SGNHC, 49 mitral valve repair operations have been performed here. There were 25 male and 24 female patients. The average age was 28.7 years (5 - 68 years). All were symptomatic with significant dyspnoea and palpitation. Other symptoms were hemoptysis in eight, peripheral embolism in one and CNS embolism in four. Associated lesions included ASD in three, an ASD and constrictive pericarditis in one and a pseudoaneurysm of the left common iliac artery with PDA in the fifth. One patient had undergone CMV nine years before presentation.